Business simulation games as digital tools for supporting school entrepreneurship education - Panoutsopoulos, H.; Lykourentzou, M.; Sampson, Demetrios (2011)
During the last few years there has been considerable interest for digital game-based learning. This interest can be attributed to the increased popularity of digital games among school students, as well as to their potential as effective learning environments for collaborative learning-by-doing activities. On the other hand, fostering entrepreneurial mindsets through teaching and learning has been a key priority for entrepreneurship education in Europe. The aim of this paper is to study the potential use of a commercial business simulation digital game, namely "Sims 2 - Open for business", in school entrepreneurship education drawing links with standard curriculum math teaching. © 2011 IEEE.